Biomechanical influence of crown-to-implant ratio on stress distribution over internal hexagon short implant: 3-D finite element analysis with statistical test - Verri, Fellippo Ramos [UNESP]; Santiago Júnior, Joel Ferreira [UNESP]; Faria Almeida, Daniel Augusto de [UNESP]; Brandao de Oliveira, Guilherme Bergamo [UNESP]; Souza Batista, Victor Eduardo de [UNESP]; Honorio, Heitor Marques; Noritomi, Pedro Yoshito; Pellizzer, Eduardo Piza [UNESP] (Elsevier B.V., 2015)
The study of short implants is relevant to the biomechanics of dental implants, and research on crown increase has implications for the daily clinic. The aim of this study was to analyze the biomechanical interactions of a singular implant-supported prosthesis of different crown heights under vertical and oblique force, using the 3-D finite element method. Six 3-D models were designed with Invesalius 3.0, Rhinoceros 3D 4.0, and Solidworks 2010 software. Each model was constructed with a mandibular segment of bone block, including an implant supporting a screwed metal-ceramic crown. The crown height was set at 10, 12.5, and 15 mm. The applied force was 200 N (axial) and 100 N (oblique). We performed an ANOVA statistical test and Tukey tests; p < 0.05 was considered statistically significant. The increase of crown height did not influence the stress distribution on screw prosthetic (p > 0.05) under axial load. However, crown heights of 12.5 and 15 mm caused statistically significant damage to the stress distribution of screws and to the cortical bone (p <0.001) under oblique load. High crown to implant (C/I) ratio harmed microstrain distribution on bone tissue under axial and oblique loads (p < 0.001). Crown increase was a possible deleterious factor to the screws and to the different regions of bone tissue. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Finite element analysis; Biomechanics; Dental implants; Analysis of variance; Implant-Supported Prosthesis Dental